Analyzing Egypt's water footprint based on trade balance and expenditure inequality. (10th October 2018) - Wahba, Shimaa M.; Scott, Kate; Steinberger, Julia K.
Abstract: Egypt is a very arid country, with a rapidly growing population driving water demand beyond its annual constant supply. According to Falkenmark Water Stress Indicator, Egypt has reached a high and chronic water scarcity level that restricts its ability to accomplish economic development goals. To this end, our study has two fundamental goals; [1] tracing the effects of Egypt Virtual Water (VW) trade on its real water availability, and [2] analyzing the effects of household consumption patterns on Egypt's water availability. We have thus conducted a consumption-based analysis of water use in Egypt, using an interregional input-output (IRIO) model between Egypt and the Rest of the World. Achieving the first goal, Egypt's National Water Footprint (NWF) and it's VW net exports for 57 sectors of production are calculated. Our results indicate that Egypt saves 8% of its NWF through imports, embodied mainly in wheat. However, Egypt virtually net exports 12% of its total available freshwater resources, embodied mainly in feed, alfalfa, and paddy rice. To understand the study second goal, households NWF per product are compared with their annual direct water use. Results indicate that they consume 11% of water directly and 89% virtually. Also, urban, and rural NWF per capita are calculated according to their different patterns of expenditure. Results show that urban NWF per capita is roughly 17% higher than that of rural households, reflecting their different consumption patterns. Urban citizens consume larger amounts of all products, excluding agricultural and textile products. The water embodied in household consumption in Egypt exacerbates the water scarcity crises. This effect is particularly seen in water reliant agricultural and animal products. Also, our results show the need to monitor international trade and the virtual flows of freshwater when exploring issues around freshwater scarcity. Highlights: Egypt saves 8% of its National Water Footprint through imports. Egypt virtually net exports 12% of its total available freshwater resources. Households consume 11% of water directly and 89% virtually. Urban households national water footprint per capita is 17% higher than rural's. Water Footprinting can be used to make national policy recommendations.